FREQUENCY OF METABOLIC SYNDROME IN TYPE 2 DIABETES AND ITS RELATIONSHIP WITH INSULIN RESISTANCE - Ahmed, Shahid; Ahmed, Syed Azhar; Ali, Nadir (Journal of Ayub Medical College Abbottabad, 2010)
Background: The metabolic syndrome is a cluster of various cardiovascular disease risk factors: diabetes and pre-diabetes, abdominal obesity, hyperlipidaemia and high blood pressure. People with metabolic syndrome are twice as likely to die from and three times as likely to have a heart attack or stroke compared with people without the syndrome. The objective of the study was to observe the frequency of metabolic syndrome (MetS) in patients with type 2 diabetes mellitus and study the relationship of insulin resistance with the metabolic syndrome and its different clinical parameters. Methods: The study was conducted at Combined Military Hospital, Malir, in about six months. Hundred and fifty-five patients with type 2 diabetes were included in the study, who were diagnosed after 25 years of age. All those suffering from any liver disease, non diabetic renal disease, thyroid hormonal disorder, advanced cardiac disease and cancers were excluded from the study. Insulin resistance was measured using homeostatic model assessment of insulin resistance (HOMA-IR) and International Diabetes Federation (IDF) criteria were used to diagnose metabolic syndrome. Results: Among 155 type 2 diabetic patients, 66.5% were having metabolic syndrome (MetS) according to IDF criteria. This frequency was significantly higher in women (84.7%) as compared to men (44.3%). Difference of means of HOMA-IR (Insulin resistance) in MetS present and MetS absent cases was statistically significant in men (p=0.02) but not in women (p=0.57), when compared through independent sample t-test. Insulin resistance (HOMA-IR) was not significantly correlated with waist circumference (r=0.24), BMI (r=0.16), triglycerides (r=0.22), HDL cholesterol (r=0.18) and HbA1c (r=0.35) but showed moderate correlation with fasting plasma glucose (r=0.44). Among 39 patients belonging to the 4th quartile of HOMA-IR, i.e., the most insulin resistant people, 79% patients had MetS according to IDF criteria, and 21% patients did not have MetS. Conclusion: It is concluded that the frequency of MetS is significantly high in patients with type 2 diabetes. Insulin resistance as measured through HOMA-IR does not show significant correlation with clinical parameters of MetS in type 2 diabetics. Keywords: Metabolic syndrome, insulin resistance, HOMA-IR, IDF criteria